Cultural Values as Advertisement Themes in International and Indian Advertising - Barthwal, Sunil; Gupta, N. L. (Indian Journal of Marketing, 2011)
The present review paper discusses the importance of cultural themes that are manifested in International and Indian advertisements. The review highlights if the advertisements have been influenced by the indigenous cultural background of the nation or not. Furthermore, the paper states through various advertisement examples across nations, the fact that culture is not immune to change, and that the advertisers are always faced with a challenge to embed the right cultural themes in advertisements with changing culture over the years. The review reiterates that standardization of advertisements across nations is not an advisable strategy. The review also explores the scope of identifying certain cultural values with respect to India, which can be probable values open to Modernism and change.